(untitled) (Scientific journal of the Fergana State University, 2024)
Building a new prosperous, democratic Uzbekistan is a task of strategic importance. The solution to this problem is in many ways closely connected with a radical improvement in the life of society in economic, political, social and legal terms. Update, improvement, i.e. modernization manifests itself through the processes of liberalization and democratization. Modernization of spheres of life, especially social and political, involves the development of society through human capital. In the history of philosophy, the criteria for changing the life of society have been the main issue. The idea of development expresses different views and approaches that have developed in relation to it. When analyzing the historical roots of the process of socio-political modernization, scientific methods such as comparison, generalization, system analysis, analysis and synthesis, induction and deduction were used. When studying this issue, the points of view that were defined on it in the works of philosophers in different periods of the development of philosophical thinking were analyzed. At the same time, the idea of development was the basis of the modernization process. Modern views on the modernization paradigm were also analyzed, and its significance in the development of civil society was studied. Specific aspects of the transition from traditional society to modern society were discussed. Based on the study of works on the topic, it was concluded that the idea of social development is interpreted as, firstly, the result of the establishment of a centralized state, secondly, human intelligence, the pinnacle of enlightenment, and thirdly, the harmony of morality and law.